Surface-passivated SBA-15-supported gold nanoparticles: Highly improved catalytic activity and selectivity toward hydrophobic substrates - Gao, J.; Zhang, X.; Yang, Y.; Ke, J.; Li, Xin Yong; Zhang, Y.; Tan, F.; Chen, J.; Quan, X. (2013)
Silanol groups on a silica surface affect the activity of immobilized catalysts because they can influence the hydrophilicity/hydrophobicity, matter transfer, or even transition state in a catalytic reaction. Previously, these silanol groups have usually been passivated by using surface-passivation reagents, such as alkoxysilanes, bis-silylamine reagents, chlorosilanes, etc., and surface passivation has typically been found in mesoporous-silicas-supported molecular catalysts and heteroatomic catalysts. However, this property has rarely been reported in mesoporous-silicas-supported metal-nanoparticle catalysts. Herein, we prepared an almost-superhydrophobic SBA-15-supported gold-nanoparticle catalyst by using surface passivation, in which the catalytic activity increased more than 14 times for the reduction of nitrobenzene compared with non-passivated SBA-15. In addition, this catalyst can selectively catalyze hydrophobic molecules under our experimental conditions, owing to its high (almost superhydrophobic) hydrophobic properties. Passive aggressive: Surface-passivated SBA-15-supported gold nanoparticles that were almost superhydrophobic, with a contact angle of 144°, were prepared by surface passivation. The catalytic activity of this catalyst was more than 14-times that of non-passivated SBA-15 for the reduction of nitrobenzene. This method is a general method for the preparation of surface-passivated catalysts. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.